(untitled) (Publicaciones en Ciencias y Tecnología, 2018)
The objective of this paper is to develop a method based on fuzzy logic for the evaluation of the efficiency of decision units (Decision Making Unit, DMU) using Data Envelopment Analysis (DEA) for the handling of inaccurate data. The Alpha-cut approach is used for efficiency assessment, and the obtained fuzzy parameters are then sorted. For the evaluation of the method’s usefulness, the data of a Hospital system and 12 DMU’s were used. This research proposes an approach for the valuation and classification of DMU’s, useful for the decision making process.